a) -7+7•(-2)-4-(-18):(-3-(-5)
b) 2:(-1)-[-3+(-5-1):(-2)]
c)(-49):(-7):(-1)+12•(-2):(-6)+14-(-2+1)
d)[-11-(-4)•(-19)]:(-1)+(-4)•[-12-72:(-4)]
Răspunsuri la întrebare
Răspuns de
0
-7+7*(-2)-4-(-18:(-3-(-5))= -7-14-4+18:(-3+5)= -7-14-4+18:2=-7-14-4+9=-21-4+9=-25+9=-16
2:(-1)-[-3+(-5-1):(-2)]= -2-[-3+(-6):(-2)]=-2-(-3+3)
=- 2-0=-2
2:(-1)-[-3+(-5-1):(-2)]= -2-[-3+(-6):(-2)]=-2-(-3+3)
=- 2-0=-2
Alte întrebări interesante
Franceza,
8 ani în urmă
Matematică,
8 ani în urmă
Franceza,
9 ani în urmă
Franceza,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă